EVALUATION OF VARIOUS SPAWN GRAINS AND LOCALLY AVAILABLE SUBSTRATES FOR THE PRODUCTION OF Pleurotus eous (Berk) Sacc. (Applied Biological Research, 2026)
Pleurotus eous (pink oyster mushroom) is an important edible mushroom known for its high nutritional value and ability to grow on lignocellulosic agro residues. However, successful cultivation largely depends on the selection of suitable spawn substrates. The present study was aimed to evaluate different grain substrates for spawn production, standardize spawn dose, and identify suitable locally available substrates for cultivation of P. eous. The experiment was conducted during 2020-2022 at the Mushroom Research Laboratory, College of Horticulture and Forestry, Neri, Hamirpur (India), using six grain substrates viz., wheat (Triticum aestivum), paddy (Oryza sativa), maize (Zea mays), kodo millet (Paspalum scrobiculatum), bajra (Pennisetum glaucum), and jowar (Sorghum bicolor), and several lignocellulosic substrates. Among the spawn grains, bajra recorded maximum linear mycelial growth (91.58 mm), highest growth rate (9.62 mm day⁻¹), and minimum spawn run period (9.33 days). Maize grain gave the highest mushroom yield (2134 g kg⁻¹ dry substrate) with biological efficiency of 213.40%. Standardization of spawn dose revealed that 3% spawn rate resulted in shortest spawn run, earliest primordia formation, and highest yield (1850 g kg⁻¹). Among locally available substrates, paddy straw gave highest yield (2803 g kg⁻¹ dry substrate) with biological efficiency of 280.3%). The study concludes that maize grain spawn with 3% spawn dose and paddy straw substrate provides an efficient and cost-effective cultivation strategy for P. eous.
Keywords: Agro-residues, biological efficiency, grain substrate, mushroom cultivation, Pleurotus eous, spawn